Combustion Modeling of Aluminum Incorporated in Low-Explosive Formulations such as Solid Propellants - Rene F. Boschi Gonçalves; Koshun Iha; José Atílio Fritz F. Rocco (Journal of Aerospace Technology and Management, 2013)
http://dx.doi.org/10.5028/jatm.v5i3.240 Aluminum that is incorporated in an energetic material such as a propellant plays a significant role in the combustion process by means of stabilization with regard to the burning and generation of additional energy. The use of simulation softwares to model the combustion mechanism and kinetic parameters of the elementary reactions that compose the oxidation were used as the pressure variation of the combustion chamber of a rocket motor conditions. The behavior of the molar fraction of the chemical species during the combustion and its posterior stabilization were observed. The systems submitted to higher pressures tend to stabilize more rapidly, according to the greater chemical speed of the elementary reactions.